Pembuatan Handicraft Dried Flower Bouqet dari Limbah Klobot Jagung dan Bunga Liar - Listiani, Putri Felita; Khabib, Arif Faisal; Setyorini, Arifah Indah; Kurniawati, Rezky; Kurniawati, Wahyu (Insan Kreasi Media, 2023)
Corn husks and wildflower waste can be used as a basic ingredient in making handicrafts if processed properly. This service activity aims to provide craft-making skills as a means of increasing student independence and creativity. The implementation methods used are input, production process, output, and evaluation. The results of this program are input, conducting market surveys to determine market conditions regarding the feasibility and shortcomings of the products produced. Next is selecting materials and providing a place, facilities, and infrastructure to support the production process. Process (production), is the process of making handicrafts starting from preparing materials and tools until they are ready to be marketed. Output, namely handicraft products that are ready to be marketed to consumers. Lastly, evaluation, at this stage, is carried out when product production has been completed by reviewing consumer responses to the product. So the PKM-K program for making handicraft dried flower bouquets from waste corn husks and wildflowers can provide students with skills so that they can process flannel cloth and turn it into an entrepreneurial idea.